Consumer Preferences on Cut Rose Purchases in Malang Raya - Ernita Dian Puspasari; Vita Regita Cahya Ningrum (Universitas Negeri Gorontalo, 2023)
Purpose: This research aims to identify the characteristics of cut-rose consumers in Malang Raya and analyze their preferences for purchasing cut-roses. Attributes for consumer preference regarding color attributes, bloom degree, and stem length.Design/Methodology/Approach: Descriptive statistics and conjoint analysis are the methods used in this research. The respondents to this research study on preferences were individuals residing in the Malang Raya region who had previously purchased cut roses. The total number of respondents in this research study was 150.Findings: The characteristics of the respondents, as indicated by the study's findings, were dominated by women aged 26 to 35 years, with incomes ranging from 3,000,000 to 6,000,000 rupiah and working in the private sector. In general, respondents stated that they purchased cut roses from florists rather than directly from farmers due to the convenience of accessibility. Consumer preference for cutting roses was obtained from a combination of red rose color attributes, a 75 percent bloom rate, and a stem length of more than 50 cm.